2002
DOI: 10.1016/s0378-1097(02)00932-1
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis: observation of coexistence of multiple viruses in the same isolate

Abstract: Trichomonas vaginalis is a flagellated, parasitic protozoan that inhabits the urogenital tract of humans. Some isolates of T. vaginalis are infected with a double-stranded RNA (dsRNA) virus, which was described in the literature as homogeneous icosahedral viral particles with an isometric symmetry and 33 nm in diameter. This study examined in detail the viral particles in T. vaginalis isolate 347 and describes a heterogeneous population of viral particles. The different dsRNA viruses were only observed after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…It has been established that the identity between T. vaginalis dsRNA virus sequences is variable, which may be expected given T. vaginalis isolates are infected with several different dsRNA viruses (Khoshnan and Alderete 1993;Benchimol et al 2002b). The virus particles observed on electron microscopic examination from the T. vaginalis ultracentrifugation retentate are consistent with the size and shape of viruses previously detected in the isolate (Benchimol et al 2002a).…”
Section: Discussionsupporting
confidence: 61%
“…It has been established that the identity between T. vaginalis dsRNA virus sequences is variable, which may be expected given T. vaginalis isolates are infected with several different dsRNA viruses (Khoshnan and Alderete 1993;Benchimol et al 2002b). The virus particles observed on electron microscopic examination from the T. vaginalis ultracentrifugation retentate are consistent with the size and shape of viruses previously detected in the isolate (Benchimol et al 2002a).…”
Section: Discussionsupporting
confidence: 61%
“…[20,21] It is suggested that T. vaginalis may be a reservoir for several different dsRNA viruses simultaneously. [22] In the present study, three unique segments (5.5, 2.5 and 1.5 kb) of dsRNA were detected. Importantly, the resolution of these segments was best achieved with dsRNA obtained during stationary phase of parasite growth, when replication of these dsRNA elements appears to be complete.…”
Section: Drug Sensitivitysupporting
confidence: 54%
“…TVV affects the total protein expression of TV, and especially the expression of cysteine proteinases and the immunogenic protein P270, which are linked to cytotoxicity, cytoadherence, and host immune evasion [15][16][17]. TVV can be divided into 4 different viral strains that have the ability to co-infect TV at the same time: TVV1, TVV2, TVV3, and TVV4 [18,19]. Each TVV strain has different effects on various aspects of TV pathogenesis.…”
mentioning
confidence: 99%